Žižek, Hegel’s Reader ... and the Show of Ideology (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This article seeks to understand Žižek’s interpretation of the German philosopher Hegel in order to explain, on the one hand, how the empire of global capitalism occurs, and on the other hand, understand the need to create a show around capitalism. Regarding these ideas, from the Science of Logic (Wissenschaft der Logik) we will analyze the concepts of immediate and reflection, which are essential (fundamental) to understand the current subjectivity. Regarding the second, we will explain how the capitalism requires the show to perpetuate himself.